Given 2 x + 2 1 3 + 2 1 0 is a perfect square number. Determine the value of x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It's not clear to me why 2 1 3 must be equal to a 2 , b 2 , or 2 a b . Most integers can be written as a sum of three terms in lots of different ways. I think it would help if you could be more specific when you introduce a and b . What are they? Are they just two integers that add up to the number being squared? Could they be any two such integers?
2^x + 2^13 + 2^10
= 2^10(2^x-10 + 2^3 + 1)
= 2^10(2^x-10 + 9)
(2^x-10 + 9) must be a square number out of this 9 is square number
to get next square number 27 add 16 to 9
so 2^(x-10) = 16 = 2^4
then x – 10 = 4 so x = 14
Actually. I used a little bit of "trial and error" thingy...... Let us assume x=10 (Case i) X<10 (Case ii) or, x>10 (Case iii). Clearly, x ≠ 10 (Substitute x = 10 and take 2^10 common, we don’t get factors for a perfect square… Case ii: x<10 Given question simplified: 2^10 [1 + 8 + 2^(10-x)] If x<10 and even, Given question would be, 2^x (2^(13-x) + 2^(10-x ) But 13 –x and 10 –x can only result in a combination of odd and even numbers.. So, we can’t have a perfect combination of even numbers. SO, x can’t be even Similarly, if x is odd, 13 –x and 10 –x can only result in a combination of even and odd numbers. So, x can’t be odd either. Therefore, x can be only greater than 10. (Case (iii) is only right) Given simplified question: 2^10 [(9 + 2^(x-10 )] 2^10 is already a perfect square. So, 9 + 2^(x-10) is a perfect square. So, That gives x = 14. (9 +16 = 25, 25 is a perfect square) X =14 is the ONLY POSSIBLE ANSWER
Sorry for the congestion of the reply.. I am in a bit of a hurry
Log in to reply
And, I can't even bring up a nice organisation of my answer, like Abhishek did !!!! :/
Problem Loading...
Note Loading...
Set Loading...
You know that a 2 + b 2 + 2 a b = ( a + b ) 2
Now this is in the form of a 2 + b 2 + 2 a b
Noe it is clear that 2 1 3 can't be a 2 or b 2 , because in a 2 or b 2 the power is even but in the other it is odd. So it is clear the 2 1 3 = a 2 = b 2
Now let us take a 2 = 2 1 0 a = 2 5
Therefore , 2 1 3 = 2 a b
or, 2 1 3 = 2 × 2 5 × b
or, 2 1 3 = 2 6 × b or 2 7 = b
Now, b = 2 7
But here as I have mentioned in the first that the given expression is expressed in the expanded form of ( a + b ) 2
Therefore, 2 x = b 2
or, 2 x = 2 7 × 2
or, 2 x = 2 1 4
or, x = 1 4
if you like this please F O L L O W me !!!!!!!!